Selection and creation of new high yield and promising varieties based on the use of the world gene pool of onion - Khurramov Ulugbek; Abdiyev Zafarali; Bolikulov Farkhod; Karimov Jamshid; Khudoyorova Khafiza; Omonlikov Alisher; Zokirov Kurbonalijon (BIO Web of Conferences)
In the article, using source of the world collection of onion, promising productive lines were selected and valuable economic characteristics were studied. In the process of studying the selected lines and conducting scientific research, the variety named “Gulkhan” was created, and the valuable economic characteristics of the new variety were highlighted.